Mechanism of Synergistic Effects of β-Lactam Antibiotic Combinations on Gram-Negative Bacilli - Farrar, W. Edmund (1973)
These studies were undertaken to elucidate further the mechanism of synergism of pairs of β-lactam antibiotics on β-lactamase-producing gram-negative bacilli. Three strains of gram-negative bacilli which elaborate β-lactamase enzymes with widely differing properties were employed. The antibacterial effects of β-lactam antibiotics, singly and in combination, on the three organisms investigated were exactly those which would have been predicted on the basis of the enzymological properties of the β-lactamases elaborated by these organisms. The findings thus support the hypothesis that the synergistic antibacterial effects of combinations of β-lactam antibiotics on these organisms were due to inhibition of the enzyme by one of the agents and killing of the organism by the other, which was protected from enzymatic hydrolysis, rather than the alternative possibility that the synergistic effects were due simply to the combined antibacterial actions of the two drugs.